Development of Micro-Pattern Gaseous Detectors for Nuclear Reaction Studies. Issue 1 (1st September 2022) - Bhattacharya, P; Sen, A; Ghosh, T K; Majumdar, N; Mukhopadhyay, S
Abstract : One of the frontiers of today's nuclear physics research is the synthesis of Super Heavy Elements (SHE). Fusion-fission dynamics, namely the competition between quasi fission and fusion is one of the key challenges to optimize the SHE. To have an insight into the dynamics, one requires the study of fission fragment mass and angular distribution near barrier energies for heavy-ion induced fission reactions. Recent successful installation of linear accelerators in India offers a unique opportunity to study the dynamics of nuclear reactions and formation process of SHE. For the effective utilization of these current, as well as upcoming facilities, development of novel detectors to study reaction dynamics, formation process of SHE with heavier projectiles and higher beam energies is needed. Gaseous detectors have undergone a rapid improvement in terms of spatial, temporal and energy resolution, rate capability, radiation hardness, ion feedback etc., ushering in a new genre of micro-structured devices based on semi-conductor technology, commonly known as Micro-Pattern Gaseous Detectors (MPGDs). Although many of the MPGD structures were primarily developed for high-rate tracking of charged particles in high energy physics experiments, stability of operation, simplicity of construction and relatively low cost make these detectors suitable for other applications, such as low-energy nuclear physics experiments. The present activities encompass a detailed evaluation of the operational conditions of Micromesh-Multi Wire and THGEM-Multi Wire hybrid detector operated in low-pressure isobutane gas with a view to optimizing their use in the detection of charged particles and fission fragments.